Knowledge of Motor Insurance among the Polish Population - Witkowska, Justyna (Olsztyn Economic Journal, 2024)
The article addresses the state of knowledge of motor insurance types and the possession of related policies among the population of Poles. The study was conducted in March 2024 on a group of 800 respondents by means of an original survey questionnaire deploying the CAWI technique. Based on the conducted survey, it was established that over 8 out of 10 respondents declared having the knowledge of Autocasco insurance (AC) and Accident insurance (NNW). The three most recognizable types of motor insurance included AC insurance, Accident insurance (NNW) and Assistance insurance. These types of insurance policies were also most frequently purchased by the surveyed. In addition to the mandatory liability insurance (OC), 95.0% of the respondents declared possession of the Accident insurance policy (NNW), 92.4% - Assistance insurance policy and 82.6% - Autocasco insurance policy.